2007
DOI: 10.1007/s10508-006-9155-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sexual Orientation Differences in Cognition Across Adulthood: Age Is Kinder to Women than to Men Regardless of Sexual Orientation

Abstract: Despite some evidence of greater age-related deterioration of the brain in males than in females, gender differences in rates of cognitive aging have proved inconsistent. The present study employed web-based methodology to collect data from people aged 20-65 years (109,612 men; 88,509 women). As expected, men outperformed women on tests of mental rotation and line angle judgment, whereas women outperformed men on tests of category fluency and object location memory. Performance on all tests declined with age b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
65
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 79 publications
10
65
1
3
Order By: Relevance
“…One, by Lacreuse et al (2005), used rhesus monkeys and showed a greater age-related decline in males than in females in a spatial delayed recognition span task. Another study, by Maylor et al (2007), using a Web-based methodology with humans, showed a steeper age-related decline in object location memory in males than in females.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 97%
See 2 more Smart Citations
“…One, by Lacreuse et al (2005), used rhesus monkeys and showed a greater age-related decline in males than in females in a spatial delayed recognition span task. Another study, by Maylor et al (2007), using a Web-based methodology with humans, showed a steeper age-related decline in object location memory in males than in females.…”
Section: Gender Differences In Episodic Memorymentioning
confidence: 97%
“…One, by Lacreuse et al (2005), used rhesus monkeys and showed a greater age-related decline in males than in females in a spatial delayed recognition span task. Another study, by Maylor et al (2007), using a Web-based methodology with humans, showed a steeper age-related decline in object location memory in males than in females.With respect to gender differences in emotional episodic memory, Hamann and Canli (2004) provided a brief review of the literature and suggested that differential amygdala activation between men and women may contribute to different levels of memory performance for emotional materials. Specifically, past research has shown that performance for emotional materials was best predicted by righthemisphere amygdala activation in men and lefthemisphere amygdala activation in women (e.g., Cahill et al, 2001;Cahill, Uncapher, Kilpatrick, Alkire, & Turner, 2004) and, in turn, that the overlap in left-lateralized activation in the amygdala and regions responsible for encoding processes may reflect greater integration of emotional Mem Cogn (2012) 40:551-566 553 content and episodic memory in women (Canli, Desmond, Zhao, & Gabrieli, 2002).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…According to [8] males score higher than females on tests that require rotating objects in mental images in psychology courses. Although it may vary by socioeconomic background [8] and sexual orientation [19], this effect occurs consistently across cultures [19] and age ranges [9]; [13], and it is a critical empirical pillar of theories of human sex differences in spatial abilities, including evolutionary theories [19]. The table figures triggered the strong argument for spatial skills diagnosis in order to come up with a tailor made programme that would introduce pre-service teachers to the relevant design skills in the subject Technology.…”
mentioning
confidence: 99%
“…Also, there are reports suggesting that the typical age-related cognitive decline is greater in men than in women (Barrett-Connor and Kritz-Silverstein, 1999;Elias et al, 1997;Van Exel et al, 2001), or the opposite (Brayne et al, 1995;Elias and Kinsbourne, 1974;Meinz and Salthouse, 1998), or equal in the two sexes (Barnes et al, 2003;Maitland et al, 2000;Singer et al, 2003). Maylor et al (2007) tested a large sample of subjects (almost 200,000) with various tasks, and found a generally steeper age-related decline in response accuracy for males than females, while the opposite was found for response speed. The study of Lacreuse et al (2005) in non-human primates showed higher male performance in spatial working memory at a young age and a greater decline with age for males than for females.…”
Section: Introductionmentioning
confidence: 99%